Implementation of a Database Security System to Prevent SQL Injection in CRUD Applications Using Laravel - T. Sukma Achriadi Sukiman; Reyhan Achmad Rizal; Cut Lika Mestika Sandy; Anni Zulfia; Annisa karima (Global Advances in Science, Engineering & Technology (GASET), 2026)
The development of information technology has driven the use of web-based applications in various sectors, but this growth has also been accompanied by an increase in cyber security threats, one of which is SQL Injection. SQL Injection is an attack technique that exploits input validation weaknesses in applications to insert malicious SQL commands into the system. This study aims to implement and evaluate a security system against SQL Injection attacks using the Laravel framework. The research method used is an experimental approach, involving the development of a simple Laravel-based CRUD application that is tested before and after the implementation of security features. The security features implemented include Eloquent ORM, parameter binding, input validation using Form Request, authentication, role-based access control, and user activity audit logs. The test results show that all SQL Injection attack attempts, both manual and automated using SQLMap, were successfully blocked by the system. In addition, the application functions optimally without performance issues, proving that the implementation of security does not hinder system operations. In conclusion, Laravel is capable of providing effective protection against SQL Injection when its security features are implemented correctly. This study also recommends strengthening against other types of attacks such as XSS and CSRF, as well as the use of data encryption to enhance overall system security.